Suomalaisia yksinlauluja = Finska solosånger = Finnish lieds - Kuula, Toivo, 1883-1918; Madetoja, Leevi, 1887-1947; Tiihonen, Kirsi; Salminen, Satu ([Kustannuspaikka tuntematon] : HNH International, 1999)
22 laulua.
r1996, Järvenpää, Järvenpää-sali.
2000-12-sibk, 2002-10-sib.
Keywords: laulut